Cover Feature: The Impact of Halogenated Phenylalanine Derivatives on NFGAIL Amyloid Formation (ChemBioChem 24/2020). (27th November 2020) - Chowdhary, Suvrat; Moschner, Johann; Mikolajczak, Dorian J.; Becker, Maximilian; Thünemann, Andreas F.; Kästner, Claudia; Klemczak, Damian; Stegemann, Anne‐Katrin; Böttcher, Christoph; Metrangolo, Pierangelo; Netz, Roland R.; Koksch, Beate
Abstract : As shown for the model peptide NFGAIL, the introduction of different fluorinated phenylalanine derivatives leads to specific amyloid‐folding kinetics through an alteration in hydrophobicity and changes in their α‐frameworks. This is represented by the clock, as its hand (the "F" for fluorine) determines the self‐assembly process. The extent of fluorination, illustrated as potential plots, acts as a dimension of change not only for aggregation kinetics, but also for the morphology of resulting fibrils, as revealed by TEM micrographs. More information can be found in the full paper by B. Koksch et al. The picture was created by S.C., Helmut Fouquet, J.M., M.B., R.R.N. and B.K.